2016
DOI: 10.1007/s11060-016-2172-3
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of bevacizumab and everolimus as treatment for patients with refractory, progressive intracranial meningioma

Abstract: Meningiomas that progress after standard therapies are challenging with limited effective chemotherapy options. This phase II trial evaluated the efficacy of everolimus plus bevacizumab in patients with recurrent, progressive meningioma after treatment with surgical resection and local radiotherapy when appropriate. Patients with recurrent meningioma (WHO grade I, II, or III) following standard treatments with surgical resection and radiotherapy received bevacizumab (10 mg/kg IV days 1 and 15) and everolimus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 17 publications
1
74
1
Order By: Relevance
“…However, a more recent effort, which includes meningioma is still underway (NCT01880749). While a phase II trial of everolimus in combination with bevacizumab showed little improvement in PFS in comparison to treatment with bevacizumab alone (NCT00972335) (83), the combination of everolimus and octreotide decreased tumor growth rate by more than 50% in 29/35 patients (NCT02333565) (84). Improved PFS was also noted, and likely merits further study.…”
Section: Molecularly-targeted Therapiesmentioning
confidence: 99%
“…However, a more recent effort, which includes meningioma is still underway (NCT01880749). While a phase II trial of everolimus in combination with bevacizumab showed little improvement in PFS in comparison to treatment with bevacizumab alone (NCT00972335) (83), the combination of everolimus and octreotide decreased tumor growth rate by more than 50% in 29/35 patients (NCT02333565) (84). Improved PFS was also noted, and likely merits further study.…”
Section: Molecularly-targeted Therapiesmentioning
confidence: 99%
“…Currently, a phase 0 clinical trial (NCT01880749) is including patients with vestibular schwannomas and meningiomas with a primary end-point to study the pharmacodynamics and kinetics of everolimus. The results of a phase II clinical trial (NCT00972335) combining bevacizumab (anti-VEGF) and everolimus in recurrent progressive meningioma have been reported [ 108 ]. The study included 17 patients with different grades of progressive and refractory meningiomas; patients received both drugs for 28 days after surgery and radiotherapy.…”
Section: Medical Treatment For Meningiomamentioning
confidence: 99%
“…Overall median progression free survival (PFS) was 22 months, and the median duration of disease stabilization was 10 months. The treatments were well tolerated overall, but 4 patients had to discontinue the treatment due to grade 1 and 2 toxicity [ 108 ]. The combination of everolimus and octreotide (somatostatin agonist) was found to significantly inhibit meningioma cell proliferation in vitro.…”
Section: Medical Treatment For Meningiomamentioning
confidence: 99%
“…Another phase II study of bevacizumab in combination with everolimus showed a best response of stable disease in 15 of 17 enrolled patients; PFS6 was 69% with median OS of 23.8 months. 127 Vatalanib, a tyrosine kinase inhibitor targeting VEGFR, has also been studied in a phase II trial with a best response of stable disease in 68.2% of patients and PFS6 of 64.3 and 37.5% in grade II and grade III patients, respectively. 128 Overall, strategies targeting VEGF appear to stabilize tumor growth in highly pretreated patients, although additional randomized studies are needed to confirm efficacy.…”
Section: Surgery and Radiationmentioning
confidence: 99%